Analisis Profil Daerah Kabupaten Klaten Tahun 2002-2005 - Priyono, Priyono; Susilo, Ihwan; Karyono, Karyono; Sigit, Agus Anggoro (Universitas Muhammadiyah Surakarta, 2006)
Klaten Regency is a regency that owning very strategic situation, that is lay between 3 (three ) metropolis (Jogjakarta, Surakarta, and Semarang). This Regency is having immeasurable properties, there are agriculture area, tourism, mining, and so on. This condition is obliging that this regency have to make an inventarisation of their properties to make a profile so thisregency can make a good decision to their region especially to their peoples. This research use secondary data analisys that collected from region statistics and by collecting data from many related institution and than it can gives some resource balance of this sub-province. Topographic condition of Klaten Regency predominated with flat and landuse which is rice field areal still majority, designate that this area is compatible used for agriculture. This condition is proved with big paddy supply which reach 300 ton per year while other agriculture product just only about tens of thousand ton. Agriculture sector is a potential sector to buils but the condition is worsed by the degradation of rice field areal with 26 hectare per year and also the increasing of the amount of resident every year that is proving the high requirement of land. Besides agriculture, this sub-province is also supported with mine and tourism sector. Mining sector are stone, clay, and sand are caused by the location of this area is in volcanic hill side. Tourism sector also contribute big Region Original Income to this Regency which progressively mount every year. By 3 (three) tourism object type, this sector can contribute Region Original Income equal to 773.674.000 rupiahs and supported with hotel facility, restaurant, and accessibility which mounting every year. However, amount of terminal which in this time there is not yet supported the demand.This Regency also experience of the increasing of economic sector, that is the financial that is the amount of Foreign Capital Proyect and Nation Capital Proyect, Region Original Income , and Brotto Regional Domestic Product that designating the increasing of people level live.